MEMBENTUK GENERASI BERKARAKTER: PERAN EKSTRAKURIKULER KEAGMAAN DALAM KEHIDUPAN SOSIAL SISWA - Lailiyah, Miradatul; Mufthi Azizah, Aulia; Mutammimah, Siti; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2025)
This article explores the strategic role of religious extracurricular activities in shaping a character-driven young generation amid the challenges of the digital era. Departing from the premise that schools can no longer function merely as spaces for knowledge transfer, this study examines how religious activities such as Islamic spirituality clubs, regular study circles, Qur’an memorization programs, and faith-based social service strengthen not only students’ religious understanding but also their social identity and patterns of interaction, including on social media. This research employs a qualitative library research method through a critical review of relevant journals, books, research reports, and scholarly articles. The findings indicate that religious extracurricular activities contribute to: (1) the expression of personal piety through religious content shared on social media; (2) the representation of students’ involvement in religious programs that builds a collective image and a religious school culture; and (3) the negotiation of Islamic identity and digital ethics when facing contemporary online interaction trends. These three practices demonstrate that students’ religious character is manifested not only in offline spaces but also in their digital footprints. The article underscores the importance of strengthening religious extracurricular programs that are integrated with digital literacy and media ethics, so that social media can be utilized as a space for da’wah, character building, and the formation of a young generation that is religious, critically aware, and socially responsible.